(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Lagos State University of Science and Technology’s architecture studio serves as an intensive academic and creative environment where students spend prolonged hours engaging in design-related activities. However, inadequate ergonomics, such as uncomfortable furniture, poor lighting, insufficient ventilation, overcrowding, and prolonged sitting, contributed to psychological stress among architecture students. This study therefore examined the relationship between workspace ergonomics and psychological stress in LASUSTECH architecture studios to improve students’ well-being and create healthier learning environments. The study adopted a mixed-method descriptive research approach. Data were gathered through questionnaires and physical observations, conducted with architecture students in selected studio spaces at LASUSTECH. Statistical tools such as frequency distribution, mean score analysis, and correlation analysis were used to analyse the data collected. The findings revealed that poor ergonomics in LASUSTECH architecture studios significantly affected students’ psychological stress levels, leading to fatigue, anxiety, reduced concentration, emotional exhaustion, and decreased academic performance. The study also identified the major ergonomic factors contributing to stress among architecture students. The study concludes that workspace ergonomics plays a significant role in enhancing students’ psychological well-being, comfort, and productivity within architecture studios. Proper ergonomic considerations in studio planning and design are therefore essential to achieving conducive, student-friendly learning environments. The study recommends that policymakers, university administrators, and educational planners establish ergonomic standards for architecture studios by improving furniture quality, lighting systems, ventilation, spatial organisation, and indoor environmental conditions within higher institutions.